2019
DOI: 10.30878/ces.v26n3a5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of caries risk factors associated with pregnancy

Abstract: Tooth decay is a serious public health problem, and identifying risk factors to the disease in pregnant women is essential. The use of the Cariogram, could contribute to implementing preventive measures to improve women’s health during pregnancy. The purpose of this study was to determine the risk to dental caries in pregnant women. The Cariogram presents the results of the five risk factors of caries, and it was observed that the patients have a 42% of chance to avoid new carious lesions and 58% could present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
3
1
0
1
Order By: Relevance
“…They examined 53 pregnant and 32 non-pregnant women and found that pregnant women had a higher risk of tooth decay than nonpregnant women. This finding supports the results of the present study (31).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…They examined 53 pregnant and 32 non-pregnant women and found that pregnant women had a higher risk of tooth decay than nonpregnant women. This finding supports the results of the present study (31).…”
Section: Discussionsupporting
confidence: 94%
“…The study emphasizes the importance of using a Cariogram to assess caries risk and supports its effectiveness in predicting future caries in pregnant women (38,39). The results align with previous research published in the literature (31,(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hal ini sejalan dengan hasil penelitian tingkat risiko karies yang dilakukan oleh Dolic et al 17 menggunakan kariogram dimana sebagian besar ibu hamil memiliki tingkat risiko karies tinggi, dimana faktor-faktor yang memiliki asosiasi yang kuat dengan tingginya risiko karies pada ibu hamil adalah pengalaman karies sebelumnya, plak, frekuensi konsumsi makanan manis, dan bakteri Streptococcus mutans. 17,18 Kateeb 19 menyatakan kurang baiknya kesehatan gigi dan mulut ibu hamil dapat disebabkan karena kurangnya pengetahuan ibu hamil bahwa kesehatan gigi dan mulut memiliki keterkaitan dengan kesehatan umum dan dapat berpengaruh pada hasil kelahiran anak-anak mereka. Selain itu kebanyakan ibu hamil juga tidak memprioritaskan perawatan gigi dan mulut karena kendala waktu dan biaya.…”
Section: Pengukuranunclassified